Role of the leukemia-inhibitory factor gene mutations in infertile women: the embryo-endometrial cytokine cross talk during implantation--a delicate homeostatic equilibrium - Králícková, M; Síma, P; Rokyta, Z (Folia microbiologica, 2005)
Locally secreted cytokines of both the embryonic and the endometrial origin control the implantation process. The defects in their signaling that lead to unfavorable environment within the uterus may cause embryo implantation failure. The leukemia inhibitory factor (LIF), interleukin-11 (IL-11) as well as IL-12/IL-15/IL-18 system are regarded to be important signaling vectors. LIF plays an essential role in the preimplantation embryo development and the blastocyst implantation and its gene mutations in women contribute to the implantation failure and subsequent infertility. IL-11 signaling has been shown to be required for the uterine decidualization response as well as for the hatching and attachment of blastocysts. The IL-12/IL-15/IL-18 system interacts with endometrial leukocytes, particularly with NK cells, and influences directly the local angiogenesis and tissue remodeling. Differences in the levels of endometrial leukocytic subpopulations and in the patterns of intra-uterine cytokine concentrations that are observed between fertile and infertile women contribute to infertility probably by affecting the embryonic maternal dialogue during the implantation and early placentation period. Focusing on this cross talk promises to open new era in assisted reproduction techniques that will be based on diagnostics of missing signaling molecules and impairments of uterine receptivity as well as on therapeutic applications of individualized embryo culture and transfer media.
Keywords: signální transdukce; Killer Cells, Natural; interleukin-6; těhotenství; ženská infertilita; Interleukin-6; cytokiny; Signal Transduction; mutace; Leukemia Inhibitory Factor; Cytokines; Endometrium; Infertility, Female; ženské pohlaví; Mutation; Humans; Pregnancy; homeostáza; endometrium; Embryo, Mammalian; leukemický inhibiční faktor; embryo savčí; implantace embrya; Female; buňky NK; Embryo Implantation; Homeostasis; lidé